2016
DOI: 10.1007/s11010-016-2906-8
|View full text |Cite
|
Sign up to set email alerts
|

Possible role of HIWI2 in modulating tight junction proteins in retinal pigment epithelial cells through Akt signaling pathway

Abstract: PIWI subfamily of proteins is shown to be primarily expressed in germline cells. They maintain the genomic integrity by silencing the transposable elements. Although the role of PIWI proteins in germ cells has been documented, their presence and function in somatic cells remains unclear. Intriguingly, we detected all four members of PIWI-like proteins in human ocular tissues and somatic cell lines. When HIWI2 was knocked down in retinal pigment epithelial cells, the typical honeycomb morphology was affected. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 54 publications
3
21
0
Order By: Relevance
“…Though increased expression of HIWI2 is reported in cervical cancer tissues, Y79 showed higher expression of HIWI2 than the levels reported in cervical cancer cells [19]. This could be attributed to the cellular origin of cancer, which correlates with the finding from our previous study showing higher expression of PIWI-like proteins in the retina than in the retinal pigment epithelium (RPE) [11]. …”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Though increased expression of HIWI2 is reported in cervical cancer tissues, Y79 showed higher expression of HIWI2 than the levels reported in cervical cancer cells [19]. This could be attributed to the cellular origin of cancer, which correlates with the finding from our previous study showing higher expression of PIWI-like proteins in the retina than in the retinal pigment epithelium (RPE) [11]. …”
Section: Discussionsupporting
confidence: 63%
“…In our previous report, we demonstrated the effects of HIWI2 silencing on the Akt pathway [11]. OTX2 is known to be activated by the PI3K/Akt signalling axis [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…piRNAs, a class of small non‐coding RNAs associated with piwi, maintain genomic integrity through transposon silencing . Most piRNA studies focus on germline and stem cells; however, a couple of studies have found that piRNAs were also expressed in somatic tissues such as liver, heart, brain and retina tissues . Piwi proteins and their associated piRNAs were demonstrated to control the beta cell functions and be involved in the development of type 2 diabetes .…”
Section: Discussionmentioning
confidence: 99%
“…45 Most piRNA studies focus on germline and stem cells; however, a couple of studies have found that piRNAs were also expressed in somatic tissues such as liver, heart, brain and retina tissues. 46,47 Piwi proteins and their associated piRNAs were demonstrated to control the beta cell functions and be involved in the development of type 2 diabetes. 48 One study identified miRNA, piRNA and other sRNAs in the eyes of adult newts and found that these sRNAs may be involved in the regeneration of a newt's lens and retina.…”
Section: Discussionmentioning
confidence: 99%